Aproximación dendroecológica y caracterización anatómica y física de la madera juvenil de Araucaria angustifolia de Oxapampa, Perú - Romero, Jordan (2025)
The study of tree growth in forest plantations for timber use must be complemented by the description of wood characteristics to serve both foresters and wood technologists. Studies based on growth rings allow for the acquisition of growth records in diameter, height, shape, and volume with annual resolution, facilitating the assessment of their relationship with environmental factors. This is crucial for thinning and harvesting decisions in forest plantations. Evaluating differences in wood characteristics in axial and radial directions provides valuable information for analyzing their optimal potential use. This study evaluated the growth of Araucaria angustifolia (Bertol.) Kuntze using dendroecological techniques. Additionally, wood anatomy and basic density were examined at four axial positions and three radial levels as quality indicators. Stem analysis revealed that CAIDBH ranged from 1.72 to 2.33 cm; MAIDBH ranged from 1.70 to 1.99 cm. The climatic variable that best explains the radial growth variability was precipitation, with a R2 of 83.82 %. A higher basic density, tracheid length, and tracheid wall thickness were found near the base and the bark. Based on these findings, A. angustifolia demonstrated promising growth and wood quality under local conditions, such as those in Oxapampa, for timber use.